Perlindungan Hukum yang Berkeadilan bagi Debitur atas Penerapan Kolektibilitas oleh Bank dalam Penggunaan Kartu Kredit - Herri Haryanto; Erry Praditya Utama (PT Elaborium Elevasi Indonesia, 2026)
This study discusses fair legal protection for debtors in the context of the application of collectibility in credit card usage in Indonesia. In practice, the collectibility method often has negative impacts on debtors, particularly in determining credit status and in debt collection practices that may exceed reasonable limits. The author analyzes the theories and legal frameworks governing credit card collectibility as well as the principles of justice in the protection of debtor consumers. The research employs a normative approach through literature studies of laws and legal doctrines. The findings show that the implementation of collectibility must prioritize the principles of fairness and proportionality so that the rights of debtors are not unilaterally harmed. The study recommends the improvement of regulations and the development of a more responsive and equitable dispute resolution mechanism for credit card debtors in default in Indonesia. It also emphasizes the need for state involvement, particularly through the Financial Services Authority (OJK), to play an active role in facilitating dialogue between creditors and defaulting debtors to find fair and effective solutions regarding collectibility.